The effect of biochar on growth performance of rice grown on contaminated soil / Ariff Ikhwan Ariffin - Ariffin, Ariff Ikhwan (Faculty of Plantation and Agrotechnology, 2019)
Cadmium is heavy metal that can cause harm to plant and human health A set of experiment was done in green house UITM Melaka Jasin to study about effect of biochar towards paddy growth performance grown on contaminated soil. Empty fruit bunch (EFB) was use as a feed stop in this experiment, bio-char are prepared under limited oxygen supply with high temperature pressure (400c – 500c). For this experiment different rate of bio-char base on ratio are used, ratio from 5 tons to 15 tone as a treatment and 0 tone as a control. The experiment was set up as Complete Randomized Design (CRD) with three replication their have 12 pots experimental unit. The growth performance MR220 was measured based on the following parameters, total number of tillers, plant height, chlorophyll content and dry weight. The data of growth parameter were collected in every 5 days after manuring which day 30th, day 50th and day 70th. By following recommendation rate from Department of Agriculture the manuring was done in day 25th, day 45th and day 65th. The biochar ability in reducing cadmium effect to paddy growth, this is because biochar is soil amendment that can absorb toxicity cause by cadmium in the same time also able in maintain soil fertility and soil moisture without cause any contamination to soil structure and help in maintain the soil sustainability. In dry mass of crop between treatment, the treatment number 4 which is treat with 15tone of biochar have high significant different with p-value 0.012.